POLYSEMY IN FROZEN (2013) MOVIE - Darojatun, Desri Utari; Nurhapitudin, Irman; Sulaeman, Dedi (CALL, 2023)
Objectives of this study were to analyze types of polysemy in the and to interpret polysemous words realized in the Frozen movie script. A method of this study was qualitative that produced descriptive data. The data were words that contained polysemy. A source of data in the study was Frozen (2013) movie scripts. The data were analyzed using suitable theories, including the type of polysemy proposed by Apresjan (1974) and meaning proposed by Lyons (1981). Based on the analysis, it was found that there are 26 pairs of data of polysemy that consist of two types of polysemy; 20 pairs of data are regular polysemy and six pairs of data were irregular polysemy. In the Frozen movie script, regular polysemy is more dominant than irregular polysemy because regular polysemy has the same systematic word but is different semantically or non-synonymous. Meanwhile, irregular polysemy has the same or true meaning as other words, and even it has no systematic relation. In conclusion, polysemy can arise in spoken or written language, so that the ambiguous word that have more than one meaning are categorized into polysemy.Â Â Keywords: polysemy, meaning, frozen, movie script, semantics